PELP1: A review of PELP1 interactions, signaling, and biology - Girard, Brian J. (2013)
Proline, glutamic acid, and leucine rich protein 1 (PELP1) is a large multi-domain protein that has been shown to modulate an increasing number of pathways and biological processes. The first reports describing the cloning and characterization of PELP1 showed that it was an estrogen receptor coactivator. PELP1 has now been shown to be a coregulator for a growing number of transcription factors. Furthermore, recent reports have shown that PELP1 is a member of chromatin remodeling complexes. In addition to PELP1 nuclear functions, it has been shown to have cytoplasmic signaling functions as well. In the cytoplasm PELP1 acts as a scaffold molecule and mediates rapid signaling from growth factor and hormone receptors. PELP1 signaling ultimately plays a role in cancer biology by increasing proliferation and metastasis, among other cellular processes. Here we will review 1) the cloning and characterization of PELP1 expression, 2) interacting proteins, 3) PELP1 signaling, and 4) PELP1-mediated biology.